Green Development in Action: A Corpus-Assisted Harmonious Discourse Analysis of “China’s Green Development in the New Era” - Yixing Liu (Journal of Linguistics and Communication Studies, 2024)
This paper examines the discourse and underlying ideologies of an official white paper called “China’s Green Development in the New Era,” utilizes a corpus-assisted method within the framework of Harmonious Discourse Analysis (HDA) from the perspectives of people-orientedness assumption and HDA’s principles of conscience, proximity, and regulation. The transitivity analysis investigates the distribution of processes, participants, and circumstances in the white paper, aims to reveal the presence of HDA’s principles and explore the conveyed concepts of green development. In addition, high-frequency words were retrieved from the corpus to reflect the themes and ideas of the paper, showing the embodiment of harmonious discourse in the text from a quantitative perspective. This study contributes to the fields of ecolinguistics and discourse analysis, providing empirical insights into ecological policy and consciousness. It also offers practical implications for translation learners, aiming to provide strategies for translating Chinese official documents related to the topic of green development.